Experiences of Intervention Against Violence An Anthology of Stories. Stories in four languages from England & Wales, Germany, Portugal and Slovenia - Hagemann-White, Carol; Grafe, Bianca (Cultural Encounters in Intervention Against Violence, 2016)
The stories in this anthology emerged from interviews with women and young people about their experience of intervention when they were escaping a situation of abuse, neglect and/or sexual exploitation. They come from the research project "Cultural Encounters in Intervention Against Violence (CEINAV)" in four countries - England & Wales, Germany, Portugal and Slovenia. Through support services the women and young people were contacted; they came from a minority or migration background and had travelled through a history of violence and intervention, and were asked to tell who intervened, what had been helpful and what had not.